The effects of acute oral glutamine supplementation on exercise-induced gastrointestinal permeability and heat shock protein expression in peripheral blood mononuclear cells - Zuhl, Micah (Cell Stress Chaperones, 2014)
Chronic glutamine supplementation reduces exercise-induced intestinal permeability and inhibits the NF-κB pro-inflammatory pathway in human peripheral blood mononuclear cells. These effects were correlated with activation of HSP70. The purpose of this paper is to test if an acute dose of oral glutamine prior to exercise reduces intestinal permeability along with activation of the heat shock response leading to inhibition of pro-inflammatory markers. Physically active subjects (N = 7) completed baseline and exercise intestinal permeability tests, determined by the percent ratio of urinary lactulose (5 g) to rhamnose (2 g). Exercise included two 60-min treadmill runs at 70 % of VO(2)max at 30 °C after ingestion of glutamine (Gln) or placebo (Pla). Plasma levels of endotoxin and TNF-α, along with peripheral blood mononuclear cell (PBMC) protein expression of HSP70 and IκBα, were measured pre- and post-exercise and 2 and 4 h post-exercise. Permeability increased in the Pla trial compared to that at rest (0.06 ± 0.01 vs. 0.02 ± 0.018) and did not increase in the Gln trial. Plasma endotoxin was lower at the 4-h time point in the Gln vs. 4 h in the Pla (6.715 ± 0.046 pg/ml vs. 7.952 ± 1.11 pg/ml). TNF-α was lower 4 h post-exercise in the Gln vs. Pla (1.64 ± 0.09 pg/ml vs. 1.87 ± 0.12 pg/ml). PBMC expression of IkBα was higher 4 h post-exercise in the Gln vs. 4 h in the Pla (1.29 ± 0.43 vs. 0.8892 ± 0.040). HSP70 was higher pre-exercise and 2 h post-exercise in the Gln vs. Pla (1.35 ± 0.21 vs. 1.000 ± 0.000 and 1.65 ± 0.21 vs. 1.27 ± 0.40). Acute oral glutamine supplementation prevents an exercise-induced rise in intestinal permeability and suppresses NF-κB activation in peripheral blood mononuclear cells.